정량적 관리 기반 무기체계 시험업무 프로세스 개선 연구 - 나태흠; 이주연; 김영민 (시스템엔지니어링학술지, 2024)
Today, the importance of test and evaluation of defense systems is increasing day by day. In performing efficient defense systems test works, process improvement based on quantitative management is essential. The purpose of this paper is to present the results of process improvement for the defense systems test works of the test organization based on quantitative management activities. As a methodology to confirm process improvement performance, the ‘MPM(Managing Performance and Measurement)’ practice area of the CMMI model was applied. The quantitative management model for defense systems test works was developed so that it could be practically applied not only to the entire test organization but also to the organization at the department level that actually performs the test work. Finally, the application cases of the quantitative management model for defense system test works and the results of process improvement were described.
Keywords: Today; the importance of test and evaluation of defense systems is increasing day by day. In performing efficient defense systems test works; process improvement based on quantitative management is essential. The purpose of this paper is to present the results of process improvement for the defense systems test works of the test organization based on quantitative management activities. As a methodology to confirm process improvement performance; the ‘MPM(Managing Performance and Measurement)’ practice area of the CMMI model was applied. The quantitative management model for defense systems test works was developed so that it could be practically applied not only to the entire test organization but also to the organization at the department level that actually performs the test work. Finally; the application cases of the quantitative management model for defense system test works and the results of process improvement were described.; Quantitative Management; Managing Performance and Measurement; Capability Maturity Model Integration; Defense Systems Test Works; Process Improvement